Factors influencing northern region bumiputra consumers purchase intention of global brands / Farah Merican Isahak Merican ...[et al.] - Isahak Merican, Farah Merican; Ruslan, Nur Dalila Husna; Md Zani, Rosliza; Nazrin, Nizar (2019)
Global brands like McDonalds, Samsung, Uniqlo, Toyota and Starbucks have long entered the Malaysia market. Consumer acceptance for these global brands are relatively strong but today’s hyper-connectivity and globalization trend brings harsher competition. Capturing a market throughout the world is not an easy task for any company. Going global and making consumer purchase your brand takes more than just being present. Majority of global brands nowadays face strong competition from local brands. In developing markets like Malaysia, global brands are seen as having more potential in capturing local consumption as consumers seem to accept and adopt the presence of global brands better. Globalization enables businesses to compete worldwide and signifies a dramatic change in consumer behavior. The dynamics of consumer behavior is gradually altered and consumers are indulged with variety of products and services. Purchasing is somehow made easy with an enormous spread of local and global brands.